Pushed news: when the news comes to the cellphone - Fidalgo, Antonio (Brazilian journalism research, 2009)
Combining two findings of recent surveys on the Internet which state that 1) “the Internet will soon surpass all other media as a main source for national and international news” and 2) “the mobile device will be the primary connection tool to the Internet in 2020” leads us to the conclusion that smartphones will soon be the primary source for news access. But if so, how will news come to the Internetconnected cellphones? In accordance with the distinction, already drawn in 1997, between push and pull technologies as two different forms of how content is delivered to the end users, cellphones are characterized as push devices (passive reception), in opposition to computers, classified as pull devices (active reception). The news items that fit cellphones are pushed news. And they will be pushed as SMS, e-mails, tweets and through news aggregators.